Urgensi Filsafat Islam dalam Pengembangan Wawasan Pemikiran Mahasiswa di Universitas Islam Negeri Sumatera Utara - Aurelia, Dinda; Adenan, Adenan; Zauldiyariza, Zauldiyariza; Ritonga, Roni Rahmat (Medan Resource Center, 2023)
The position of philosophy in Islam sees the ebb and flow of praise and criticism it is necessary to discuss it. Harmonization of philosophical and Islamic themes, harmonization of experience in long discussions. Some scholars argue that Islam and philosophy are completely different and that Islam and philosophy have areas that cannot be combined. But few try to harmonize and synthesize the two, starting with Al-Kind, continuing with AlFarab and ending with Ibn Sina and Ibn Rushd. Al-Kindi believed that the goal of philosophy was to discover the true nature of things through causal explanations. Al-Kindi brought religion (Islam) with philosophy, arguing that philosophy is the science of truth and religion is also the science of truth. At the same time, Al-Farab succeeded in reconciling classical Greek political philosophy with Islam, which was understood in the context of revealed religions. Avicenna argued that God created the world through emanations. Based on the opinions of these philosophers, this study explains that philosophy and religion (Islam) as part of science have a close and harmonious relationship with one another.